Periplocymarin Alleviates Doxorubicin-Induced Heart Failure and Excessive Accumulation of Ceramides - Yun, Weijing; Qian, Lei; Yuan, Ruqiang; Xu, Hu (Frontiers in Cardiovascular Medicine, 2021)
Doxorubicin-driven cardiotoxicity could result in dilated cardiomyopathy and heart failure (HF). Previously, we showed that periplocymarin exerted a cardiotonic role by promoting calcium influx and attenuating myocardial fibrosis induced by isoproterenol (ISO) by improving the metabolism of cardiomyocytes. However, the impact of periplocymarin on doxorubicin (DOX)-triggered cardiomyopathy has not been investigated. In the current study, C57BL/6 mice were randomly divided into three groups, namely, the control, DOX, and DOX+periplocymarin groups. The cardiac function and apoptosis were measured. Our results revealed that periplocymarin administration greatly improved the DOX-induced cardiac dysfunction manifested by the ejection fraction (EF%), fractional shortening (FS%), left ventricular posterior wall thickness (LVPW), left ventricular anterior wall thickness (LVAW), left ventricular (LV) mass, and attenuated DOX-induced cardiomyocyte apoptosis assessed by hematoxylin and eosin (H&E) staining, terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining, and western blotting. Further study using H9c2 cells revealed that the pretreatment of periplocymarin suppressed DOX-induced apoptosis evidenced by annexin V staining. Moreover, liquid chromatography with tandem mass spectrometry (LC-MS/MS) analysis demonstrated that DOX lead to an accumulation in serum ceramide, and the pre-treatment of periplocymarin could reverse this phenomenon. Network pharmacology also demonstrated that ceramide metabolism was involved in the process. Consistently, real-time PCR showed that periplocymarin significantly abolished the induction of the genes involved in the de novo synthesis of ceramide, i.e., CerS2, CerS4, CerS5, and CerS6, and the induction was attributed to the treatment of DOX. Collectively, these results suggested that periplocymarin reduced cardiomyocyte apoptosis to protect hearts from DOX-induced cardiotoxicity and the de novo synthesis of ceramides was involved in this process.